2014
DOI: 10.1039/c4an00638k
|View full text |Cite
|
Sign up to set email alerts
|

Large scale infrared imaging of tissue micro arrays (TMAs) using a tunable Quantum Cascade Laser (QCL) based microscope

Abstract: Chemical imaging in the field of vibrational spectroscopy is developing into a promising tool to complement digital histopathology. Applications include screening of biopsy tissue via automated recognition of tissue/cell type and disease state based on the chemical information from the spectrum. For integration into clinical practice, data acquisition needs to be speeded up to implement a rack based system where specimens are rapidly imaged to compete with current visible scanners where 100's of slides can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 15 publications
(14 reference statements)
0
83
0
Order By: Relevance
“…Nevertheless, we are currently developing FTIR acquisition with new devices, such as infrared focal plane arrays, making it possible to reduce acquisition time and consequently, increase the spatial resolution. 26 It has been reported that visual assessment of IF with scoring (IFTA) according to the Banff classification suffers from poor interobserver reproducibility. 3,27 Moreover, the use of a small number of grades to describe the severity of individual histologic injuries may lack sensitivity during the early stage of IFTA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we are currently developing FTIR acquisition with new devices, such as infrared focal plane arrays, making it possible to reduce acquisition time and consequently, increase the spatial resolution. 26 It has been reported that visual assessment of IF with scoring (IFTA) according to the Banff classification suffers from poor interobserver reproducibility. 3,27 Moreover, the use of a small number of grades to describe the severity of individual histologic injuries may lack sensitivity during the early stage of IFTA.…”
Section: Discussionmentioning
confidence: 99%
“…If the information content is highly localized in the spectral domain, large increases in throughput can be achieved. Bassan et al showed that a Spero Ò microscope is able to collect single-wavenumber images of a breast tissue microarray that contains more than 26 million spectra in 540 seconds, compared with more than 17 hours using an FTIR microscope (15). This allowed an entire biopsy sample covering an area of 20£24 mm to be imaged with 4 micron pixel size in 9 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Correlative IR/SMLM studies are expected to become significantly more approachable with new benchtop light-sources that are brighter than traditional Globars and thus deliver better signal-to-noise faster allowing for nonsynchrotron live-cell experiments 52,53 . Furthermore, robust water absorption correction 54 will allow for examination of the Amide I band and better elucidation of changes to protein composition.…”
Section: Discussionmentioning
confidence: 99%